Efeito de um programa de corrida em nível de treinamento desportivo sob a composição corporal de adultos com sobrepeso e obesidade - Ribeiro, Mateus Duarte (2021)
Building training protocols for effective weight loss is still a challenge. Current data indicate that the weight loss process is multifactorial, in which at least caloric balance (nutritional intake and expenditure on physical activities / exercises) participate, motivational factors (engagement with the program), physiological and genetic factors, in the case of physical training, even the nature of the training load is a determining factor. Thus, the objective of this study will be to evaluate the potential of a running training program based on the sports training methodology, on adherence to the program and its outcomes in body composition, considering nutritional factors (food consumption), physiological factors (systemic inflammation and oxidative stress), and behavioral (sedentary behavior) in people with obesity and / or overweight. For this, 100 volunteers will be evaluated regarding nutritional habits (food recall), aerobic capacity and anaerobic threshold (ergospirometry), body composition (anthropometry and bioimpedance), biochemical profile (blood collection) and behavioral aspects (questionnaire). Then, the experimental group will start a training program with a sports approach for 24 weeks, meanwhile, a control group will perform stretching and relaxation sessions. In the middle (12 weeks), as well as at the end, all assessment procedures will be repeated. For the control of the training load, at the beginning of each month the experimental group will be monitored by questionnaires and by heart rate records. For data analysis, we will use statistical techniques to calculate measures of central tendency and dispersion (mean and standard deviation). The KolmogorovSmirnov and Levene test will be performed to verify the normality and homogeneity of the data, respectively. if the data are normal, a two-way ANOVA variance test will be performed for repeated measures, with Tukey's post hoc. Pearson's correlation test. If the data are not normal, a non-parametric statistic with equivalent tests will be applied. Statistical analyzes will be performed by the statistical program SPSS for Windows (Version: 25.0, PASW Statistics SPSS, Chicago, IL, EUA). Significance Level will be set at 5%.